EFEKTIVITAS BAHAN AJAR TEMATIK SEKOLAH DASAR BERBASIS BUDAYA LOKAL MELALUI PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP AKTIVITAS BELAJAR SISWA - Rumiris Lumban Gaol; Ester Julinda Simarmata (Universitas Negeri Medan, 2019)
Abstract: Effectiveness of Using Local-Based Thematic Primary School-Based Teaching Materials Through the Application of Contextual Teaching and Learning (CTL) Learning Model for Student Learning Activities. In this study analyzed the effectiveness of local culture-based primary school thematic teaching materials through the application of the contextual teaching and learning learning model (CTL) to student learning activities. This research method is a mixture of quantitative and qualitative methods with a simple linearity analysis on the assessment sheet of teaching materials and observations of student learning activities. The population and sample in this study were all elementary school students in grade IV SDN 156315 Sosorgadong 5, Sosorgadong District, Barus Tapanuli Tengah, North Sumatra. Data collection techniques in this study were observation by distributing questionnaires to students. The conclusion of the research on effective teaching materials on learning activities is seen from the influence of variables x and y, namely the effectiveness of the use of local culture-based thematic teaching materials on student activities.Keywords: Local Thematic Teaching Material, Contextual Teaching and Learning (CTL) Learning Model, Student Learning ActivitiesAbstrak: Efektivitas Penggunakan Bahan Ajar Tematik Sekolah Dasar Berbasis Budaya Lokal Melalui Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Aktivitas Belajar Siswa. Dalam penelitian ini menganalisis efektivitas bahan ajar tematik sekolah dasar berbasis budaya lokal melalui penerapan model pembelajaran contextual teaching andlearning (CTL) terhadap aktivitas belajar siswa. Metode penelitian ini adalah metode campuran yaitu metode kuantitatif dan kualitatif dengan analisis uji linieritas sederhana pada lembar penilaian terhadap bahan ajar dan pengamatan terhadap aktivitas belajar siswa. Populasi dan sampel pada penelitian ini adalah adalah semua siswa SD kelas IV SDN 156315 Sosorgadong 5 Kecamatan Sosorgadong Barus Tapanuli Tengah Sumatera Utara. Teknik pengumpulan data pada penelitian ini adalah observasi dengan menyebarkan angket kepada siswa. Simpulan penelitian bahan ajar efektif terhadapat aktivitas pembelajaran dilihat dari pengaruh variabel x dan y yaitu adanya efektivitas penggunaan bahan ajar tematik berbasis budaya lokal terhadap aktivitas siswa.Kata Kunci: Bahan Ajar Tematik Budaya Lokal, Model Pembelajaran Contextual Teaching And Learning (CTL), Aktivitas Belajar Siswa